Audiological results of endoscopic surgical repair of the long process of incus - Badi Aldosari (KeAi Communications Co., Ltd., 2017)
Objective: The purpose of this study is to evaluate our experience with endoscopic repair of ossicular discontinuity at the incudostapedial joint, with or without an intact stapes suprastructure, and present our hearing results. We classify results based on the causative pathology, the type of ossiculoplasty, and type of lesion. We demonstrate the ability to endoscopically place a total ossicular replacement prosthesis (TORP), measuring 4.25 mm, between the stapes footplate and the incus remnant to reestablish ossicular continuity. Methods: This was a retrospective case series conducted in tertiary referral center (Hopital de la Timone) Marseille, France. 25 patients underwent incudostapedial rebridging ossiculoplasty between 2009 and 2013. Fifteen cases of chronic otitis media and 10 otosclerosis revisions were included in the study. Three different materials were used in ossiculoplasty, hydroxyapatite cement, incus remnant, and partial/total ossicular replacement prostheses. Audiometric results were evaluated before and after ossiculoplasty. Twelve month follow-up data is provided. Results: The mean postoperative air-bone gap was 15 dB (5–25 dB). Hearing results were better inotosclerosis revisions. Hydroxyapatite cement produced an air-bone gap of 5 dB, TORP placed under the incus produced a 12 dB gap, and TORP placed under the malleus resulted in a 12 dB gap and one deaf ear. In cases of chronic otitis media, the residual air-bone gap was 17 dB with PORP, 12 dB with TORP, and 20 dB with incus transposition. Conclusion: The hydroxyapatite cement is effective in the reconstruction of ossicular discontinuity but the high price limits its utilization. TORP placed under the incus is a reliable and stable method of ossicular reconstruction that is cost effective and offers satisfactory hearing results in selected patients.